Distributed adaptive tracking control for high-order multi-agent systems with unknown dynamics. Issue 9 (2nd September 2017) - Gu, Jianzhong; Li, Wuquan; Yang, Hongyong
ABSTRACT: In this paper, we investigate the adaptive tracking problem of high-order multi-agent systems with unknown parameters and unknown nonlinear functions. Under the assumption that the leader is the root of a spanning tree, a distributed adaptive controller with tuning function is constructed recursively based on backstepping design method. The designed controller can guarantee that the tracking errors and the parameter errors eventually converge to an arbitrarily small compact set by choosing design parameters. A simulation example demonstrates the effectiveness of the design scheme.